Efficacy of the intracamerally administered mydriatics for cataract surgery in patients with primary open-angle glaucoma. Issue 3 (May 2023) - Ripa, Matteo; Cuffaro, Giovanni; Savastano, Maria Cristina; Grieco, Giulia; Rizzo, Stanislao; Ricci, Francesco
Purpose: To compare Mydrane®, mydriatic eye drops, and Mydriasert® in terms of pupil site stability, surgical time, visual field, and anterior chamber configuration modifications among patients with primary open-angle glaucoma (POAG) during cataract extraction surgery. Methods: Retrospective analysis of sixty patients with POAG and cataract who underwent elective cataract extraction. All patients underwent routine ophthalmic examinations, including automatic visual field examination, anterior chamber configuration, specular microscopy, and arterial blood pressure measurement prior to surgery, and 24 h and 30 days postoperatively. All cataract surgeries were video-recorded and all measurements were performed using a media player. Patients divided into groups 1, 2, and 3 (n = 20 in each group) received topical mydriatic eye drops, Mydriasert®, and an intracameral injection of Mydrane®, respectively, immediately after the first incision. Results: The mean change in pupil size from just before capsulorhexis to the end of surgery was 0.43 ± 0.09, 0.42 ± 0.08, and 0.36 ± 0.02 mm in groups 1, 2, and 3, respectively. The mean surgery duration was similar among all the groups. The baseline main cell density slightly decreased at 24 h and remained stable for 30 days postoperatively. The mean deviation and pattern standard deviation remained stable at 1 month after surgery. At 24 h after surgery, the nasal irido-corneal angle, temporal-iridocorneal angle, and anterior chamber depth increased compared with the baseline, remaining stable for 30 days after surgery. Conclusions: Mydrane® produced adequate and stable mydriasis as effectively as produced by Mydriasert® and topical eye drops.